PENGARUH PENDIDIKAN, SKALA USAHA, PELATIHAN AKUNTANSI DAN UMUR USAHATERHADAP PENGGUNAAN INFORMASI AKUNTANSI (Studi Empiris Pada UMKM Kota Pekanbaru) - Erick Aderson Pasaribu; Kamaliah Kamaliah; Adhitya Agri Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research was to identify and analyze about (1) The influence of owner education on the use of accounting information (2) The influence of scale business on the use of accounting information (3) The influence of accounting training on the use of accounting information and (4) The influence of age business on the use of accounting information. Population in this research is MSMES in Pekanbaru district.. The method that used to the sample selection was purposive sampling method. The number of samples in this research were 91 respondents. The type of data used in this study is primary data. Data collection techniques used survey techniques by distributing questionnaires. Data analysis techniques used in this research was multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 22.0 for Windows as data processing software program. Results of hypothesis test using statistical t-test showed the significant value of owner education variable 0.905> 0.05, which means that H1 not accepted, the scale business variable 0.000 < 0.05, which means that H2 accepted, accounting training variables 0.000 < 0.05, which means the H3 accepted, and age business variables 0.516 > 0.05 which means that H4 not accepted. The results showed owner education and age business has not effect on the use of accounting information, scale business and accounting has effect on the use of accounting information.Keywords : Owner Education, Scale Business, Accounting Training, Age Business and Accounting Information